Population structure of croakers fish (Family: Sciaenidae) from fish boats at Nusantara Fishery Port, Merauke Regency - Modesta R. Maturbongs,; Marius A. Welliken K,; Nurdini Sholikatun Nisa, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This study aims to determine the structure of body size based on length and weight class, length-weight relationship, and the condition factor of croaker fishes, the Sciaenidae family landed at the Merauke Nusantara Fisheries Port. Sampling was conducted from June to September 2020 using a random sampling method. The data analysis used in this study included the length and body size structure of the croaker fishes, the length-weight relationship, and the condition factor. Croaker fishes landed at the Nusantara Fisheries Port, Merauke Regency, obtained 2 species, namely Nibea saldado and Johnius amblycephalus with a total sample size of 170 individuals. Nibea saldado's body length ranges from 210-665 mm with body weights ranging from 200-2,500 grams, while Johnius amblycephalus has body length ranges from 570-740 mm with body weights ranging from 1,800-4,000 grams. The long-weight relationship of Nibea saldado and Johnius amblycephalus in June - Setember showed negative allometric growth, but for Johnius amblycephalus in July the growth was allometric positive. The condition factor for Nibea saldado has a value range between 0.645 - 2.874, while Johnius amblycephalus has a value range between 0.291 - 1.079. Keywords: Population structure, croaker fishes, Sciaenidae, Nusantara Fisheries Port, Merauke.